Photoelectrochemical fabrication of porous GaN and their applications in ultraviolet and ammonia sensing - Beh, Khi Poay; Yam, Fong Kwong; Tan, Lay Kim; Ng, Siow Woon; Chin, Che Woei; Hassan, Zainuriah (Japanese Journal of Applied Physics, 2013)
This article reports the studies of porous GaN fabricated using photo-electrochemical anodization method and their applications in UV and ammonia gas sensing. GaN was anodized under different durations and their fundamental aspects were investigated. Electron micrographs revealed that the porous surface was obtained, however prolonged anodization durations would lead to breakdown of porous layer, forming nanostructures. A plausible pore formation and breakdown mechanism were proposed based on current-transient profile. In Raman spectroscopy, forbidden bands such as E1(TO) and A1(TO) were noted in anodized samples. The intensity of these bands was dependent on the geometrical position of the nanostructures formed on porous surface. In UV and ammonia sensing studies, change in Schottky barrier height was the greatest for anodized samples. Porous GaN in UV sensing was 5 times more sensitive relative to as-grown GaN. In ammonia sensing, porous GaN displayed positive results even in the absence of catalytic metal, Pt. © 2013 The Japan Society of Applied Physics.
CRIS-Team Scopus Importer:2022-11-02